A bizarre sternorrhynchan wing from the Lower Jurassic of Luxembourg (Hemiptera: Sternorrhyncha: Pincombeomorpha?). (3rd July 2019) - Szwedo, Jacek; Weis, Robert; Nel, André
Abstract: Fossil wing of Hemiptera Sternorrhyncha with peculiar venation is described from the lower Toarcian (Lower Jurassic) of Bascharage (Grand-duchy of Luxembourg). It represents new family Xulsigiidae fam. nov., comprising a new genus and species Xulsigia karetsa gen. et sp. nov. It is placed preliminarily in extinct infraorder Pincombeomorpha for the presence of three branches of median vein. Key to families of Pincombeomorpha is given and the taxonomic position and venation features of the new fossil are discussed. Family Xulsigiidae is registered in Zoobank under thehttp://www.zoobank.org/urn:lsid:zoobank.org:act:3A57B428-638A-439A-AEC4-D18B5959B5CA Genus Xulsigia is registered in Zoobank under thehttp://www.zoobank.org/urn:lsid:zoobank.org:act:2B255A30-5A7C-4CF8-AE77-18ED6E8E03C2